Alteration in Indole Metabolites After Cardiopulmonary Bypass Surgery in Neonates and Infants - Leroue, Matthew K.; Maddux, Aline B.; Lehmann, Tanner; Niemiec, Sierra; Mancuso, Christopher A.; Khailova, Ludmila; Mourani, Peter M.; Klawitter, Jelena; Davidson, Jesse A. (Critical care explorations, 2025)
IMPORTANCE: Cardiopulmonary bypass (CPB) surgery is associated with changes in the intestinal microbiome. Metabolism of tryptophan into the indole pathway is entirely facilitated by the intestinal microbiome, and indole metabolites play a critical role in intestinal epithelial integrity, intestinal and systemic vascular tone, and intestinal and systemic immune response. OBJECTIVES: To evaluate the impact of CPB on microbial-derived indole metabolites and their association with clinical outcomes. DESIGN, SETTING, AND PARTICIPANTS: Prospective cohort study of neonates and infants younger than 6 months of age undergoing CPB at a quaternary children's hospital. MAIN OUTCOMES AND MEASURES: Serum samples underwent quantitative pathway mapping via mass spectroscopy. Clinical outcomes of interest included cardiac ICU (CICU) length of stay and Vasoactive-Inotropic Score (VIS) at 48 hours. RESULTS: Ninety patients between 2 and 169 days old were enrolled. Patients showed significant postoperative changes in seven of eight indole metabolites. A two-fold increase in preoperative levels of indole-3-carboxylic acid was associated with 0.63 odds of requiring vasoactive medications at 48 hours (p = 0.023) and among those subjects still requiring vasoactives at 48 hours, they had an average 7.1% decrease in VIS at 48 hours (p = 0.005), and a 12.25% reduction in CICU length of stay (p = 0.001). Higher levels of indole-3-carboxylic acid preoperatively and at 24 and 48 hours postoperatively were also significantly associated with decreased CICU length of stay. Conversely, increased levels of several metabolites, including indole-3-lactic acid, indole-3-carbaldhyde, indole-3-propionic acid, tryptamine, and tryptophol, in the preoperative and postoperative period were associated with higher VIS at 48 hours and increased CICU length of stay. CONCLUSIONS AND RELEVANCE: CPB was associated with significant changes in indole metabolite levels postoperatively. Indole-3-carboxylic acid, which suppresses T-regulatory (Treg) differentiation, is associated with improved patient outcomes, whereas other metabolites, that promote Treg differentiation, were associated with worse outcomes.